Competitiveness of rapeseed, soybeans and palm oil - Yelto Zimmer, (Journal of Oilseed Brassica, 2026)
With increasing global demand for vegetable oils for both food and biofuels, the question arises what rawmaterials are the most competitive ones. Based on “agri benchmark” data, the cost of production forsoybeans, rapeseed and oil palm are calculated. A cross crop comparison has to cope with the fact that thesecrops contain two high value components: vegetable oil and protein. Therefore, the allocation of cost is doneaccording to the value shares of the two components. One is the cost of raw material for one tonne ofrapeseed oil, which is in the range of 1,000 to 1,200 USD/t for Western European farms. Farms in EasternEurope and Australia are spending 500 to 700 USD/t. In soybeans, cost of production varies between 400 and800 USD/t. These figures compare to palm oil, where cost of production is 300 USD/t. With regard to theimpact of energy prices and greenhouse gas emissions, the productivity of nitrogen in these crops iscompared. While in rapeseed one tonne of vegetable oil requires about 100 kg of nitrogen, in palm oil thisfigure is only 30 kg/t. The nitrogen cost per tonne of raw material is 40 USD/t in palm oil but 100 USD/t inrapeseed. Only soybeans are much better because they don’t get fertilized with nitrogen at all